Pengaruh Brand Awareness dan Kualitas Produk terhadap Loyalitas Pelanggan Melalui Kepuasan Konsumen Pakaian H.A.R.V Official di Manado - Anjelika Prisilia Lengkong; Riane Johnly Pio; Joanne V. Mangindaan (Universitas Sam Ratulangi, 2021)
H.A.R.V Official is one of the MSME fashion products in the city of Manado. H.A.R.V produces various kinds of headwear, t-shirts, jackets/hoodies, bags, pants to socks. The consistency of issuing new products or articles every month and also being frequently involved in community events has made H.A.R.V widely known among the millennials of Manado city. Just like fashion businesses in general, H.A.R.V wants its product sales to continue to increase, but in fact, there is fluctuation in the sales of H.A.R.V Official products. This study aims to determine the effect of brand awareness, product quality on customer loyalty through customer satisfaction. This research uses a descriptive quantitative research method with a total sample of 100 respondents obtained using the purposive sampling technique. Data analysis using SPSS version 20. The results showed that brand awareness has an effect on consumer loyalty; product quality affects consumer loyalty; brand awareness and product quality together have an impact on consumer satisfaction; Brand awareness and product quality affect customer loyalty with customer satisfaction as the interviewing variable.